Teknik Periwayatan Hadis sebagai Landasan Pembelajaran Berbasis Sanad dalam Pendidikan Islam - Palengkey, Rahmi Dewanti; Miro, Abbas Baco; Rahayu, Anita; Rahim, Sumarni (Universitas Muhammadiyah Makassar, 2025)
This study aims to examine the technique of hadith transmission as the foundational basis for sanad-based learning in Islamic education. Hadith, as the second principal source of Islamic teachings after the Qur'an, requires a high degree of authenticity and validity in its transmission process. Utilizing a descriptive qualitative approach through library research, this study analyzes various transmission methods such as sima’, qira’ah, ijazah, munawalah, and others, along with the moral and intellectual requirements that must be met by narrators. The findings reveal that the techniques of hadith transmission not only function as a means of scholarly verification but also form an educational system emphasizing authoritative knowledge continuity, ethical values, and the spiritual bond between teacher and student. The sanad-based learning model plays a vital role in safeguarding the integrity of knowledge transmission, particularly amid the challenges of the digital era saturated with unverified information. Thus, integrating the principles of hadith transmission into today’s Islamic educational systems is highly relevant as a revitalization of classical Islamic educational traditions. Keywords: hadith transmission, sanad, Islamic education, knowledge transmission, learning.